PENGGUNAAN METODE LUAS BANGUN DATAR UNTUK MENINGKATKAN PENGUASAAN KONSEP KEMAMPUAN MENYELESAIKAN SOAL GERAK LURUS - Eka Pusparini; Tomo Djudin; Muhammad Musa Syarif Hidayatullah (Universitas Tanjungpura, 2021)
AbstractThis research was conducted at SMA Negeri 8 Singkawang with the aim of finding outwhether the use of the area of the flat shape method is effective for students to improvetheir mastery of concepts and the ability to solve graphic problems in straight motionmaterial. This research was conducted because it was obtained information that theability of students in a straight motion graph is still very low. Then the research samplewas 25 students of class X MIPA 1 SMA Negeri 8 Singkawang by providing instrumentsin the form of test questions in the form of essays with indicators of mastery of theconcept of straight motion and the ability to solve straight motion graph questions. Itwas found that the use of the flat shape method has an effect (with high category) sothat it is effectively used to improve concept mastery and the ability to solve straightmotion graph form problems. With an increase of 15,6 for the mastery of the concept ofstraight motion and 16,24 for the ability to solve problems in the form of graphs forstraight motion material. The effectiveness of the use of the flat area method to improvethe mastery of concepts and the ability to solve graphic from problems in straight motionmaterial is relatively high because students find it easier to use the flat wake areamethod.Keywords: Flat Area Method, Concept Mastery, Ability to Solve Graphic Problems,Straight Motion